10.20886/jphh.2018.36.2.129-138 - Jamal Balfas; Efrida Basri; Adi Santoso (BRIN Publishing, 2018)
The use of wood filler is vital in wood finishing. However, the most commercial wood fillers available in the market are made of chemical solvent-based resins, such as polyurethane and nitrocellulose. These products contain volatile organic compounds. This study examines performance of alternative and commercial wood fillers. The alternative wood fillers were made from the mixture of putty powder and organic resins, i.e. shellac, acrylic and polyvinyl acetate. The wood fillers were tested on tusam, jabon and rubber wood by assessing their physical, mechanical and chemical performances in comparison with the most commercial wood filler, i.e. nitrocellulose wood filler. Samples of three wood species were treated by spreading them with various wood filler solutions. Weight and dimensional changes due to treatment were determined in wet and dry sample conditions. Chemical and scratch resistance of the wood filler films were also tested to determine their chemical and mechanical performance. Color similarity of the wood filler treated samples and control were evaluated using the CIELab color system. The effect of treatment were varied according to wood species. Tusam samples possess greater weight and dimensional gains than those of jabon and rubber wood samples. All organic wood filler formula could effectively protect wood from water intrution, comparable to that of the commercial wood filler (WF). The organic wood fillers had higher scratch resistance, less chemical resistance, and better color appearance than the commercial WF.